Highlighting circular cities trends in urban planning. A review in support of future research tendencies - Marzani, Giulia; Tondelli, Simona (TeMA - Journal of Land Use, Mobility and Environment, 2024)
Circular economy is seen as an opportunity of overcoming the traditional linear model of consumption and production based on the “take-make-dispose” model, in favour of a more sustainable use of resources. It is acknowledged that the city scale is relevant in this transition towards circularity, even if there is a lack of implementation of the circular city through plans and policies. A higher understanding of the interrelations between circular economy and urban planning is therefore needed. This study, through a scoping review and a bibliometric analysis, allowed to systematize and analyse the knowledge about the existing trends in planning circular cities and to identify gaps for future research. What emerged is that a methodology to integrate circular economy principles into urban planning tools and procedures still does not exist in literature, even though some recurrent decision-making framework are frequently used and the topic is currently under debate.